Ruskin Bond as a writer of short stories - Dr Kiritsinh P. Thakor (The Creative Launcher, 2019)
This paper focuses on the view of ‘Ruskin Bond as writer of short stories’. In the modern age, the short stories highly impressed to the whole world. It is a highly complex form of literature and it has considered technically today, has been a very challenging form of literature. A short story is a type of prose fiction, which has grown up beside the fiction, and it has its own value and recognized place in literature today. Ruskin Bond is known internationally as one of India’s most prolific writers in English for children, adults and young adults. His short stories are well-finished and integrated works of art in literature. His plots are not well constructed but his characters are appearing to be the living women and men to the nature. Most of his stories depend upon the characters and His work provides an insight or outside into universal themes such as the tension between present and past, culture elements, city life versus rural values, the dignity of ordinary folk song, preservation of the environment, and the living in harmony with nature.